Pengaruh Metode Pembelajaran dan Sikap Sosial Terhadap Hasil Belajar Sejarah Siswa SMAN 12 Tangerang Selatan - Naijan Naijan (Jurnal Pendidikan Sejarah, 2014)
Abstract The aim of the study is to reveal the empirical data about the effect of instructional methodology and student’s social attitudeon the outcome of history learning on the students of SMAN 12 Tangerang Selatan. The methodology used is the experimental method with a 2x2 treatment design. Research instrumentation will include a test that will be used to measure student’s learning outcome, and a questionnaire that will be used to measure student’s social attitudeon history outcomes. A total of 36 participants will be randomly selected. Data analysis will be performed by using two way variance analysis. The findings of the study will be demonstrate: 1) a higher student’s history learning outcome of those who were taught by Cooperative Learning method typeJigsawcompared to those who were taught by conventional method. 2) There is an interaction effect between instructional methodology and student’s social attitudeon history learning outcome. 3) History learning outcome of students who has positive social attitudeand were taught by Cooperative Learning method typeJigsaware higher than those with the same level of social attitude but were taught by conventional method. 4) History learning outcome of students who has negative social attitudeand were taught by Cooperative Learning method typeJigsaware not below those with the same social attitude but were taught by conventional method. Keywords : history learning outcome, history instructional methodology, student’s social attitude, cooperative learning methodtipe Jigsaw, cooperative learning